Wybrane instrumenty rachunkowości zarządczej w kształtowaniu relacji z klientami - Putyra, Adam (Selected Instruments of Managerial Accounting in Creating Relationships with Customers, 2008)
In a dynamic and turbulent modern reality companies should replace a product-centricity with customer-centric approach. Such reorientation requires significant organizational changes and widely adopted customer relationship management system. In such interdisciplinary system managerial accounting should play a significant role by offering an integrated set of instruments that place a customer in the centre of their analysis. The article presents selected instruments of managerial accounting which could be valuable element of company-wide system that supports customer relationship management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 115-127